Performance, Breast Morphological and Carcass Traits in the Ardennaise Chicken Breed - Lariviere, J.M.; Farnir, F.; Detilleux, J.; Michaux, C.; Verleyen, V.; Leroy, P. (International Journal of Poultry Science, 2009)
The aim of this study was to quantify performance, breast morphological and carcass traits in Belgium’s most ancient chicken breed: the Ardennaise. Evaluation during growing showed at 84 days of age light as-hatched mean live Body Weights (BW) (1115g ± 221), fairly high Feed Conversion Ratio (FCR) (5.09 ± 0.4) and Liveability (LIV) (92.55% ± 4.6). At 85 days, male and female in vivo breast measurements such as Keel Angle (KA) (67.74-71.82o), Thoracic Circumference (TC) (25.61-28.05 cm), Keel Length (KL) (10.32-11.26 cm) and muscle thickness (TM) (10.70-12.11mm), with associated BW, were all greater in males and significantly different between sexes (p